An empirical analysis of consumer motivation towards reverse exchange. Issue 2 (14th March 2016) - Yuan, Ruizhi; Liu, Martin J; Chong, Alain Yee-Loong; Tan, Kim Hua
Abstract : Purpose: – Despite the growing interest in reverse exchange, studies on the subject from the perspective of consumer participation and motivation remain sparse. Consumers' participation in reverse exchange is a key component of supply-chain reverse logistics. To address the gap in existing studies, this paper aims to empirically identify the intention and causes of consumer electronic product exchange (EPE). The proposed research model incorporates value-belief-norm and neutralization theories, linking consumers' values to their intentions to participate in EPE. Design/methodology/approach: – Survey data collected from 250 consumers were analyzed using structural equation modeling. Findings: – This discussion shows that people are more likely to present positive attitudes when they are ethically concerned. However, this tendency is not without exceptions and behavior influenced by ethics was not always observed. Upon examination, the findings highlight moderating forces of psychological tension that arise when people behave in ways that are in apparent contradiction to their expressed positive attitudes. Research limitations/implications: – It is important to modify the model by analyzing consumers' actual EPE behaviors. Future research should also reconsider the results from a longitudinal perspective. Practical implications: – The reverse logistics management practices proposed offer valuable insight into other various activities as well, including an integrated supply chain model and improving customer service. Social implications: – The proposed action of EPE encourages consumers as well as managers to reduce, recycle or effectively dispose of waste. Originality/value: – Current reverse exchange models are insufficient for measuring consumer motivations perspective, which is a key but inadequately researched perspective of determining the effectiveness of reverse logistics management. This research endeavors to fill this gap and augment previous studies in EPE by advancing the discussion on how the concept of reverse logistics management is evaluated and justified in relation to consumption values and psychological motivations.